Tinjauan Literatur Sistematis tentang Pneumoconiosis Di Kalangan Pekerja - Fahmi Nofriandi (Jurnal Ilmu Kesehatan Abdurrab, 2024)
Pneumoconiosis, a group of lung diseases caused by inhalation of mineral dusts, remains a significant occupational health concern globally. This systematic literature review aims to synthesize current knowledge on the prevalence, risk factors, clinical manifestations, diagnosis, and preventive measures of pneumoconiosis among workers. The review identifies gaps in existing research and highlights the need for comprehensive strategies to prevent and manage the disease.